Accelerated Bone Regeneration by Adrenomedullin 2 Through Improving the Coupling of Osteogenesis and Angiogenesis via β-Catenin Signaling - Wang, Feng; Wang, Wenbo; Kong, Lingchi; Shi, Li; Wang, Mengwei; Chai, Yimin; Xu, Jia; Kang, Qinglin (Frontiers in Cell and Developmental Biology, 2021)
Both osteogenic differentiation and the pro-angiogenic potential of bone marrow mesenchymal stem cells (BMSCs) contribute to bone regeneration during distraction osteogenesis (DO). Adrenomedullin 2 (ADM2), an endogenous bioactive peptide belonging to the calcitonin gene-related peptide family, exhibits various biological activities associated with the inhibition of inflammation and the attenuation of ischemic-hypoxic injury. However, the effects and underlying mechanisms of ADM2 in osteogenic differentiation and the pro-angiogenic potential of BMSCs, along with bone regeneration, remain poorly understood. In the present study, we found that osteogenic induction enhanced the pro-angiogenic potential of BMSCs, and ADM2 treatment further improved the osteogenic differentiation and pro-angiogenic potential of BMSCs. Moreover, the accumulation and activation of β-catenin, which is mediated by the inhibition of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and the activation of protein kinase B (AKT), have been shown to contribute to the effects of ADM2 on BMSCs. In vivo, ADM2 accelerated vessel expansion and bone regeneration, as revealed by improved radiological and histological manifestations and the biomechanical parameters in a rat DO model. Based on the present results, we concluded that ADM2 accelerates bone regeneration during DO by enhancing the osteogenic differentiation and pro-angiogenic potential of BMSCs, partly through the NF-κB/β-catenin and AKT/β-catenin pathways. Moreover, these findings imply that BMSC-mediated coupling of osteogenesis and angiogenesis may be a promising therapeutic strategy for DO patients.